Are Borderline Personality Symptoms Associated With Compulsive Sexual Behaviors Among Women in Treatment for Substance Use Disorders? An Exploratory Study. Issue 10 (5th April 2016) - Elmquist, JoAnna; Shorey, Ryan C.; Anderson, Scott; Stuart, Gregory L.
Abstract : Objective: Extant literature has documented a significant relationship between borderline symptoms and substance use disorders. As supported in past work, there is a significant theoretical relationship between borderline symptoms and compulsive sexual behaviors because both disorders share common underlying behaviors and traits. There is no known research that has examined the empirical relationship between borderline symptoms and compulsive sexual behaviors in a population with substance use disorders. To fill this important gap in the literature, this relationship was examined in the current study. Method: Medical records from 120 women admitted to a private, residential treatment program for substance use disorders were reviewed for the current study. Results: Hierarchical multiple regression analysis demonstrated that borderline symptoms were significantly associated with compulsive sexual behaviors after controlling for alcohol use and problems, drug use and problems, age, and positive impression management. Conclusion: Results from this study provide potentially important research and clinical implications, which could ultimately aid treatment and reduce relapse. However, continued research is needed to further examine the relationship between symptoms and compulsive sexual behaviors.